PEMANFAATAN RAPOR PENDIDIKAN UNTUK MENGIDENTIFIKASI RENDAHNYA CAPAIAN GEOMETRI AKM NUMERASI SISWA SMP - Fahruh Juhaevah; Alimin Tarwa; Idris Tatawalat; Nur Samsia Tomu; Sarfa Wassahua (JURNAL MathEdu (Mathematic Education Journal), 2026)
The Education Report presents learning outcomes down to the content domain level, yet schools rarely use it to diagnose weaknesses in student numeracy, and even less so in geometry. This study mapped the geometry achievement profile in AKM Numeracy, traced the factors accompanying low achievement, and formulated recommendations for improving instruction. An explanatory sequential mixed methods design was used. The first phase analysed indicators from the 2025 Education Report of SMP Negeri 10 Tual using descriptive quantitative analysis. The second phase explained the resulting patterns through semi-structured interviews with students and mathematics teachers, analysed thematically following the interactive model of Miles, Huberman, and Saldana. The quantitative phase showed that 79.17% of students had not reached the minimum numeracy competency and that the geometry score fell from 50.64 in 2024 to 47.51 in 2025. The lowest achievement occurred in knowing (40.68) and applying (46.53), while reasoning rose by 3.28 points. Interviews with students and teachers indicated that the main difficulties stem from poor reading of visual representations, mastery of shape properties relying solely on rote memorization, and limited use of interactive learning media in the classroom. The Education Report can therefore serve as a diagnostic instrument supporting data-driven decision making for geometry learning in junior secondary schools. AKM numeracy, data-driven decision making, Education Report, geometry, Van Hiele theory